Improving Students' Interest In Learning Javanese Character By Using Augmented Reality - Halim, David Kristianto; Chandrawati, T. Brenda; Nugroho, Erdhi Wirdayanto (Journal of Business and Technology, 2024)
Javanese script is one of the materials taught in Javanese language lessons starting from elementary school to high school starting to be taught Javanese script. However, many students feel that this lesson is very boring and difficult for students because of the atmosphere when learning and teaching methods that only see from books and listen to lighting from teachers. Therefore, research was conducted by developing an Augmented Reality (AR) system, so that later it could add innovation in the method of teaching Javanese script in order to grow interest in students and students in learning[1]. The game created is called "AJAR (Javanese Aksara AR)" in this AR contains images of each basic level script, videos that contain how to write the script correctly, examples of writing the script in a correct sentence and some practice questions that are used to help measure how much the student's ability to learn the script after using this AR.The game development method uses waterfall and this game testing method is qualitative by interviewing several sources to get data on whether this game has been successful and has met the target according to the purpose of this AJAR game. From the results of the interview it can be seen that on average all sources feel satisfied and like the existence of this AJAR game because it can help in learning Javanese script more easily and not get bored quickly.